Understanding the interaction of proteins to ion exchange chromatographic supports: A surface energetics approach. (31st January 2022) - Aasim, Muhammad; Khan, Muhammad H.; Bibi, Noor Shad; Fernandez‐Lahore, Marcelo
Abstract: Ion exchange chromatography is one of the most widely used chromatographic technique for the separation and purification of important biological molecules. Due to its wide applicability in separation processes, a targeted approach is required to suggest the effective binding conditions during ion exchange chromatography. A surface energetics approach was used to study the interaction of proteins to different types of ion exchange chromatographic beads. The basic parameters used in this approach are derived from the contact angle, streaming potential, and zeta potential values. The interaction of few model proteins to different anionic and cationic exchanger, with different backbone chemistry, that is, agarose and methacrylate, was performed. Generally, under binding conditions, it was observed that proteins having negative surface charges showed strong to lose interaction (20 kT for Hannilase to 0.5 kT for IgG) with different anionic exchangers (having different positive surface charges). On the contrary, anionic exchangers showed almost no interaction (0–0.1 kT) with the positively charged proteins. An inverse behavior was observed for the interaction of proteins to cationic exchangers. The outcome from these theoretical calculations can predict the binding behavior of different proteins under real ion exchange chromatographic conditions. This will ultimately propose a better bioprocess design for protein separation.